23.1k views
4 votes
G with the definition of covariance, prove cov[(ay − b),(cy − d)] = accov(x, y ), where x, y are random variables and a, b, c, d are constants.

User Joni Jones
by
5.8k points

1 Answer

1 vote

By definition of covariance,



\mathrm{Cov}(X,Y)=\mathbb E[(X-\mathbb E[X])(Y-\mathbb E[Y])]



\mathrm{Cov}(X,Y)=\mathbb E[XY-\mathbb E[X]Y-X\mathbb E[Y]+\mathbb E[X]\mathbb E[Y]]=\mathbb E[XY]-\mathbb E[X]\mathbb E[Y]


We have



\mathbb E[(aX-b)(cY-d)]=\mathbb E[acXY-adX-bcY+bd]


=ac\mathbb E[XY]-ad\mathbb E[X]-bc\mathbb E[Y]+bd



\mathbb E[aX-b]=a\mathbb E[X]-b



\mathbb E[cY-d]=c\mathbb E[Y]-d



\mathbb E[aX-b]\mathbb E[cY-d]=ac\mathbb E[X]\mathbb E[Y]-ad\mathbb E[X]-bc\mathbb E[Y]+bd


Putting everything together, we find the covariance reduces to



\mathrm{Cov}(aX-b,cY-d)=ac(\mathbb E[XY]-\mathbb E[X]\mathbb E[Y])=ac\mathrm{Cov}(X,Y)


as desired.

User Merugu Prashanth
by
6.0k points